PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PENJUALAN PADAUKM BATIK DI KOTA SEMARANG - Marskal Riski Hermawan; Hari Susanta Nugraha; Widiartanto Widiartanto (Universitas Diponegoro, 2017)
Although Micro, Small, and Medium Enterprises (MSME) are one of the most important parts of Indonesia’s economy, their development faces many challenges. Low capacity of human resources and their knowledge in the field of technology or management are few examples of their challenges. Currently, the knowledge is the main asset in entrepreneurship.The objective of the study is to understand the influence between Intellectual Capital and the performance of MSME in the field of Batik in Semarang, Indonesia. The study uses explanatory research with a sample of 30 entrepreneurs in the field of batik in Semarang. The sampling technique used is purposive Sampling.In this study, Intellectual Capital is classified into three categories; Human Capital, Structural Capital and Custumer Capital. Those categories and the performance of MSME are scored based on the questionnaires distributed to the entrepreneurs. The influence between each category of Intellectual Capital and the performance of MSME, and their individual contribution are also quantified. To the performance of MSME, the Human capital has influence (2,771) and contribution (21,5%), the Structural capital has influence (2,518) and contribution (16,8 %), and the Customer Capital has influence (2,381) and low contribution (16,8%). The degree of freedom of those three categories when tested simultaneously is 2,97. This value shows a positive correlation between those three categories and the performance of batik MSME in Semarang.The conclusion of the study is that there is a positive correlation between Intellectual Capital and the performance of batik MSME in Semarang. The entrepreneurs in the field of batik need to strengthen the motivation of their batik craftsmen to follow training courses so that they can compete against the other batik craftsmen outside Semarang. The quality of the craftsmen can be improved by giving them information about training courses and motivation so they gradually increase their knowledge and skills in batik production.